Mental health treatments and the influence of culture: portrayals of hypnotherapy and electroconvulsive therapy in Singaporean television dramas - Matthews, Graham John (2024)
Stigma is one of the chief reasons for treatment-avoidant behaviour among people with mental health conditions. Stigmatising attitudes are spread through multiple determinants, including but not limited to: (i) individual beliefs; (ii) interpersonal influences; (iii) local cultural values and (iv) shared culture such as depictions in television shows. Our research indicates that popular television shows are currently understudied vectors for narratives that alternately reify or debunk assumptions and stereotypes about people with mental health conditions. Although such shows are fictional, they influence perception by normalising 'common sense' assumptions over extended periods of time. Consequently, representations of patients, psychiatrists and treatments influence knowledge and understanding of mental health and treatment-seeking behaviour. While storytelling about sickness can inspire possibilities and bestow meaning on traumatic experiences, fictional narratives written without sufficient care can have the inverse effect of curtailing horizons and limiting expectations. Problematic portrayals of patients, mental health professionals and psychological interventions are often reductive and may increase stigma and prevent treatment-seeking behaviour. This article analyses the representation of hypnotherapy and electroconvulsive therapy (ECT) in Singaporean television dramas that attract a wide, mainstream audience. Our diverse team investigated dramas in all four of the official languages of Singapore: English, Mandarin Chinese, Bahasa Melayu and Tamil. We found that depictions of hypnotherapy tend to produce problematic images of mental health professionals as manipulative, able to read minds, engaging in criminal behaviour, lacking in compassion and self-interested. Meanwhile, representations of ECT typically focus on the fear and distress of the patient, and it is primarily depicted as a disciplinary tool rather than a safe and effective medical procedure for patients whose condition is severe and refractory to pharmacotherapy and behavioural interventions. These depictions have the potential to discourage treatment-seeking behaviour-when early intervention has found to be crucial-among vulnerable populations.